Schizophrenia and Dental Health: A Systematic Review. Issue 9 (September 2021) - Comparelli, Anna; Stampatore, Lorenzo; Costacurta, Micaela; Pompili, Maurizio
Abstract : Abstract: Schizophrenia is characterized not only by psychopathological symptoms but also by medical comorbidities. Among the latter, there are limited data on dental health. We conducted a systematic review with the primary aim of clarifying the extent of the relationship between dental diseases and schizophrenia. The second aim was to delineate an intervention program based on illness-related factors that influence dental health. The preferred reporting items for systematic reviews and meta-analyses statement for reporting systematic reviews was used. Only articles published in English language peer-reviewed journals were considered; we excluded case reports, meta-analyses, and systematic reviews, as well as studies that did not clearly report statistical analysis, diagnostic criteria, or the number of patients included. Twenty-one studies comprising 13, 110 patients with schizophrenia and 9025 healthy controls were included. Negative symptomatology, long duration of illness, smoking habit, drug-induced xerostomia, and neuroinflammation are the most critical areas. We suggest an intervention program for prevention and treatment of dental diseases in schizophrenia.